The Bile Acid Metabolism of Intestinal Microorganisms Mediates the Effect of Different Protein Sources on Muscle Protein Deposition in Procambarus clarkii - Xiaodi Xu; Xiaochuan Zheng; Qunlan Zhou; Cunxin Sun; Aimin Wang; Aimin Zhu; Yuanyuan Zhang; Bo Liu (Microorganisms)
The most economically important trait of the Procambarus clarkii is meat quality. Protein deposition is essential in muscle growth and nutritional quality formation. The effects and potential mechanisms of feed protein sources on crustaceans’ muscle protein deposition have not been elucidated. This study established an all-animal protein source (AP) and an all-plant protein source group (PP), with a feeding period of 8 weeks (four replicates per group, 45 individuals per replicate). The results demonstrated that muscle protein deposition, muscle fiber diameter, and hardness were significantly higher in the PP group (p < 0.05). The transcript levels of genes involved in protein synthesis were notably upregulated, while those of protein hydrolysis and negative regulators of myogenesis notably downregulated in PP group (p < 0.05). Furthermore, protein sources shaped differential intestinal microbiota composition and microbial metabolites profiles, as evidenced by a significant decrease in g_Bacteroides (p = 0.030), and a significant increase in taurochenodeoxycholic acid (TCDCA) in PP group (p = 0.027). A significant correlation was further established by Pearson correlation analysis between the g_Bacteroides, TCDCA, and genes involved in the MSTN-mediated protein deposition pathway (p < 0.05). In vitro anaerobic fermentation confirmed the ability of the two groups of intestinal flora to metabolically produce differential TCDCA (p = 0.038). Our results demonstrated that the ‘Bacteroides-TCDCA-MSTN’ axis may mediate the effects of different protein sources on muscle development and protein deposition in P. clarkii, which was anticipated to represent a novel target for the muscle quality modulation in crustaceans.